If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4x + -9 = -5 + -6x Reorder the terms: -9 + -4x = -5 + -6x Solving -9 + -4x = -5 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. -9 + -4x + 6x = -5 + -6x + 6x Combine like terms: -4x + 6x = 2x -9 + 2x = -5 + -6x + 6x Combine like terms: -6x + 6x = 0 -9 + 2x = -5 + 0 -9 + 2x = -5 Add '9' to each side of the equation. -9 + 9 + 2x = -5 + 9 Combine like terms: -9 + 9 = 0 0 + 2x = -5 + 9 2x = -5 + 9 Combine like terms: -5 + 9 = 4 2x = 4 Divide each side by '2'. x = 2 Simplifying x = 2
| 10x+4=4x+7 | | 3(2m-4)=2m+4m-4 | | .75a+.75a+a=15 | | 9v-8(1+6v)= | | 24+2y+13=20+4y-19 | | 4(n+1)+3=-35-2n | | 3(2+r)-2r=2r+11 | | 8y-16=5y+2 | | 7(t-5)+8t=5(3t+5)-13 | | 13*k=52 | | 2x-5y+z=5 | | 5(k-2)-2(k+4)=6 | | 7+5x=-33 | | 10u-6=2(5u-3) | | y-19=-3y-12 | | 2x+52=90 | | w+3/5+4=6 | | 2y+5=-14 | | -6(p+8)=-6p+12 | | -4(y-1)+-3=25 | | 0.9=0.4x | | 3(5n+3)=5n-11 | | .35*90=l | | 4x-6(5-x)=14 | | v^2+2v+49=0 | | 5+3x=7x+21 | | 3y-5+10=36 | | 7*2+2(3x-2)=133 | | 19x+-9=180-9 | | 7(1.50x)=29.50 | | .60*80=h | | 8z+7-7z=55-7z |